Acute Ischemic Stroke Secondary to Glioblastoma: A Case Report. Issue 1 (February 2014) - Pina, Sofia; Carneiro, Ângelo; Rodrigues, Tiago; Samões, Raquel; Taipa, Ricardo; Melo-Pires, Manuel; Pereira, Cláudia
Glioblastoma is a malignant infiltrative glial tumor occurring most often over 50 years of age, with diverse clinical presentations. We describe a case of temporal lobe glioblastoma with a rare presentation as an acute ischemic stroke, discussing the imaging and histopathological findings, and reviewing the literature. A 77-year-old woman had sudden onset of left hemiparesis and hemihypoesthesia. The neuroradiological studies revealed an acute ischemic lesion in the right lenticulostriate arteries territory and a right anterior temporal lobe tumor, enhancing heterogeneously after contrast with enhancement of the right middle cerebral artery wall. Histopathological analysis of the resected temporal lesion revealed a glioblastoma multiforme with tumoral infiltration of the vascular wall. Glioblastoma should be considered in the etiology of acute ischemic stroke, where neuroimaging plays an important diagnostic role, enabling a more immediate therapeutic approach, with a consequent impact on survival.